Counselor Readiness and Diagnosis in The Psychhotherapy Counseling Process in Education - Mustika, Humaira; Karneli, Yeni; Hariko, Rezki (Widyagogik, 2023)
Readiness to provide counseling and psychotherapy is indicated by the fulfillment of several requirements. Counseling can only be initiated when people recognize the need for change and are ready to engage in the change process. A psychological diagnosis provides information about the client's current problems or conditions, such as the possible causes of the client's problems, techniques used, and the counselor's predictions about the client's future outcomes or behavior, and also includes the client's strengths. This research method uses a literature review, where a literature review is a written summary of journal articles, documents, and books that explain theories and data that have occurred in the past or are currently developing. The purpose of the results and discussion of this article is to determine the extent of counselor readiness in the diagnostic process in psychotherapeutic counseling.